Intraoperative biophotonic imaging systems for image-guided interventions - Sajedi, Salar (Nanophotonics, 2018)
Biophotonic imaging has revolutionized the operation room by providing surgeons intraoperative image-guidance to diagnose tumors more efficiently and to resect tumors with real-time image navigation. Among many medical imaging modalities, near-infrared (NIR) light is ideal for image-guided surgery because it penetrates relatively deeply into living tissue, while nuclear imaging provides quantitative and unlimited depth information. It is therefore ideal to develop an integrated imaging system by combining NIR fluorescence and gamma-positron imaging to provide surgeons with highly sensitive and quantitative detection of diseases, such as cancer, in real-time without changing the look of the surgical field. The focus of this review is to provide recent progress in intraoperative biophotonic imaging systems, NIR fluorescence imaging and intraoperative nuclear imaging devices, and their future perspectives for image-guided interventions.